SLA and cost-aware cloud service provisioning through matching game and TOPSIS model - Karim, Rifat Shahriar; Rhythm, Shabab Hossain; Islam, MD.Rakibul; Kawwshik, Kazi Asif Ahmed (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.